The triangular nexus of trade, institutional quality and economic growth in China-ECOWAS and US-ECOWAS relations - Baafi, Joseph Antwi; Acheampong, Kwame; Sarkodie, Eric Effah (Edelweiss Applied Science and Technology, 2024)
This study explores the relationship between trade, institutional quality, and economic growth in the ECOWAS region from 2000-2022, with a focus on trade interactions with China and the US. Using the AMG estimator and IV-2SLS methods, the study disaggregates trade data into imports and exports and categorizes institutional settings as either strong or weak. Results indicate that trade with China and the US positively impacts ECOWAS economies, especially through imports. The positive effects are amplified in countries with strong institutional frameworks. To foster economic growth, policymakers should strengthen governance, enhance transparency, and reduce corruption. Emphasizing trade diversification and supporting export-oriented industries, alongside financial sector reforms, are crucial for sustainable development. This study offers a detailed analysis of how trade and institutional quality interact to influence economic growth in ECOWAS, providing critical insights for institutional reforms and trade strategies in the region.